2020
DOI: 10.17816/jowd69233-42
|View full text |Cite
|
Sign up to set email alerts
|

Operative vaginal delivery: outcomes for mothers and newborns

Abstract: Hypothesis/aims of study. The frequency of surgical abdominal delivery in Russia, as in the world, continues to grow, reaching 29.3% in 2017. Operative vaginal delivery is an alternative to abdominal delivery in the second stage of labor. This study was aimed at analyzing the outcome of labor for mothers and newborns using different operative vaginal delivery methods. Study design, materials and methods. We studied 293 cases of childbirth in the period from 2015 to 2018. Three groups were distinguished: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
2
0
0
Order By: Relevance
“…The common unfavourable fetal outcomes are poor 5th minute Apgar score, admission to NIC, need for the new-born resuscitation, and fresh new-born. This nding was supported by the study conducted in Russia [27],…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The common unfavourable fetal outcomes are poor 5th minute Apgar score, admission to NIC, need for the new-born resuscitation, and fresh new-born. This nding was supported by the study conducted in Russia [27],…”
Section: Discussionsupporting
confidence: 63%
“…This systematic review and meta-analysis showed that the PSSOL, maternal exhaustion/poor pushing effort, maternal cardiac problem, preeclampsia and eclampsia, fetal asphyxia, and big baby (> 4000g) were the common indications for OVD in sub-Saharan Africa. This nding was supported by the study from Turk [19], Nepal [20], India [25], another study from India[26], Russia [27], and the United Kingdom [22].…”
Section: Discussionsupporting
confidence: 54%